The Experience of Distance Learning in the Belarusian State Economic University - A. M. Sedun; E. A. Grinevich; A. I. Vereshchako (Цифровая трансформация)
Nowadays distance learning exists in various modifications. This article discusses an alternative technology of distance learning in the educational institution “BSEU”, which is to organize a rhythmic educational process with constant contact of students and teachers. The proposed technology is implemented with students on the basis of the first higher education with a shortened period of study. The material describes in detail the stages of design of the educational process and the stage of its practical implementation with students of speciality 1 24 01 02 “Law” and 101 07 “Economics and management of the enterprise”. The described technology allows in practice to provide a weekly controlled educational process in the intersessional period, which leads to an increase in the quality of performance of students compared to part-time students, as well as a decrease in the duration of the session and reduce the cost of learning.